2018
DOI: 10.1016/j.ijpsycho.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Relevance and uncertainty jointly influence reward anticipation at the level of the SPN ERP component

Abstract: The stimulus-preceding negativity (SPN) component reflects the anticipatory phase of reward processing. Its amplitude is usually larger for informative compared to uninformative upcoming stimuli, as well as for uncertain relative to predictable ones. In this study, we sought to assess whether these two effects, when combined together, produced a synergistic effect or rather independent ones on the SPN during performance monitoring. Participants performed a speeded Go/NoGo task while 64-channel EEG was recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 51 publications
4
24
1
Order By: Relevance
“…These supplementary results clearly showed that these FRN effects were not simply mirrored by earlier SPN effects occurring prior to feedback onset. In line with our previous study (Walentowska et al, ), we found that the SPN was larger (i.e., more negative) in anticipation of positive than negative feedback but exclusively when positive feedback had a high probability. These control analyses therefore support the interpretation that salience influenced feedback processing after its onset (at the FRN level) but not prior to it (at the SPN level).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These supplementary results clearly showed that these FRN effects were not simply mirrored by earlier SPN effects occurring prior to feedback onset. In line with our previous study (Walentowska et al, ), we found that the SPN was larger (i.e., more negative) in anticipation of positive than negative feedback but exclusively when positive feedback had a high probability. These control analyses therefore support the interpretation that salience influenced feedback processing after its onset (at the FRN level) but not prior to it (at the SPN level).…”
Section: Discussionsupporting
confidence: 93%
“…A valid objection could be that expectancy or probability already shaped feedback processing before the onset of the FRN. To rule out this alternative account, we ran a set of auxiliary analyses during the prefeedback interval (see supporting information, Appendix ) where we focused on the stimulus‐preceding negativity (SPN) component, which is sensitive to reward anticipation (Brunia, ; Brunia, Hackley, van Boxtel, Kotani, & Ohgami, ; Brunia & van Boxtel, ) and feedback informativeness (Walentowska et al, ). These supplementary results clearly showed that these FRN effects were not simply mirrored by earlier SPN effects occurring prior to feedback onset.…”
Section: Discussionmentioning
confidence: 99%
“…Confirming the results of all six previous experiments that examined the effect of agency on SPN (Chen et al, ; Masaki et al, ; Mei et al, ; Mühlberger et al, ; Walentowska et al, ; Yi et al, ), we found larger amplitudes when participants were encouraged to believe that their responses could influence trial outcomes. The effect was numerically largest at right, lateral prefrontal sites, just as it was in the three previous studies that portrayed the choice minus no‐choice difference topographically (Masaki et al, ; Mühlberger et al, ; Walentowska et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…The finding of SPN enhancement during choice conditions, in which a sense of agency is engendered, as compared to no‐choice conditions has been replicated and extended (Chen et al, ; Mei, Yi, Zhou, Liu, & Zheng, ; Mühlberger, Angus, Jonas, Harmon‐Jones, & Harmon‐Jones, ; Walentowska, Paul, Severo, Moors, & Pourtois, ; Yi, Mei, Li, Liu, & Zheng, ). The present study was intended to test the hypothesis that anterior insula contributes to the SPN agency effect.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation